2011
DOI: 10.1074/mcp.m110.001628
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide YFP Fluorescence Complementation Screen Identifies New Regulators for Telomere Signaling in Human Cells

Abstract: Detection of low-affinity or transient interactions can be a bottleneck in our understanding of signaling networks. To address this problem, we developed an arrayed screening strategy based on protein complementation to systematically investigate protein-protein interactions in live human cells, and performed a large-scale screen for regulators of telomeres. Maintenance of vertebrate telomeres requires the concerted action of members of the Telomere Interactome, built upon the six core telomeric proteins TRF1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 83 publications
7
100
0
1
Order By: Relevance
“…Hence, the presence of Ape1 at telomeres may reflect the amount of BER running in telomeres during routine cell metabolism. Supporting our finding that Ape1 associates with the members of the telomere complex such as TRF2 and POT1, Ape1 was identified as a protein interacting with the core telomere proteins including TRF2 (35). Furthermore, shelterin proteins TRF1, TRF2, and POT1 have been recently shown to stimulate Ape1 endonuclease activity on a telomeric abasic substrate in vitro (36).…”
Section: Discussionsupporting
confidence: 68%
“…Hence, the presence of Ape1 at telomeres may reflect the amount of BER running in telomeres during routine cell metabolism. Supporting our finding that Ape1 associates with the members of the telomere complex such as TRF2 and POT1, Ape1 was identified as a protein interacting with the core telomere proteins including TRF2 (35). Furthermore, shelterin proteins TRF1, TRF2, and POT1 have been recently shown to stimulate Ape1 endonuclease activity on a telomeric abasic substrate in vitro (36).…”
Section: Discussionsupporting
confidence: 68%
“…They then tagged the 300 genes with FLAG tag and coexpressed them individually with their respective GST-tagged bait proteins, determining results by GST pull down. They found that about 72% of the interactions found using BiFC could be verified by GST pull down [27,68]. We conducted largescale, high-precision screening of the proteins interacting with EHEC O157:H7 EspF, using a BiFC platform and flow-sorting technology for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…A number of proteomics studies have confirmed the architecture and composition of the shelterin complex, and linked telomere function to as many as over three hundred activities believed to participate in telomere integrity. [50][51][52][53] Notably, pathways linking shelterin with the ubiquitin-proteasome pathway, the DNA damage response, RNA processing and other systems have been uncovered. In this review, we focus on some of these pathways, all confirmed by proteomic studies and analyzed by cell and biochemical methods for which an important functional and mechanistic picture has emerged.…”
Section: Tankyrase: Separating Sister Telomeres At the Right Timementioning
confidence: 99%